Effect of TiC addition on microstructure and properties of CX stainless steel prepared by selective laser melting - WANG Shanchen; ZHU Weiqian; LI Xiaofeng; WANG Jianhong (Fenmo yejin jishu)
The effect of TiC addition (0, 2%, 4%, and 6%, mass fraction) on the microstructure and mechanical properties of the CX stainless steels fabricated by selective laser melting (SLM) was investigated by X-ray diffraction (XRD) analysis, scanning electron microscopy (SEM), and electron back-scattered diffraction (EBSD) in this paper. The results indicate that the addition of TiC significantly influences the grain size of CX stainless steels, thereby affecting the mechanical properties. As the TiC content increases, the average grain size of CX stainless steels decreases from 2.08 μm to 0.94 μm, 0.66 μm, and 0.71 μm, respectively, with the maximum reduction of 68.3%. The hardness of CX stainless steels gradually increases with the higher TiC content, reaching the maximum of HV0.5 491, which represents the 63.1% improvement compared to the original printed CX stainless steels. The tensile strength initially increases and then decreases with the increase of TiC content, peaking at 1574 MPa when the TiC content is 4%, which represents the 58.2% improvement compared to the original printed CX stainless steels. The fracture elongation first increases and then decreases with the higher TiC content, reaching the maximum of 16.8% at 2% TiC, showing the 29% improvement compared to the original printed CX stainless steels. When the TiC content is 4%, the CX stainless steels exhibit the optimal comprehensive mechanical properties as the yield strength of 1081 MPa, tensile strength of 1574 MPa, and hardness of HV0.5 360, representing the improvements of 21.1%, 58.2%, and 21.5%, respectively, compared to the original printed CX stainless steels.